Biologically and mechanically driven design of an RGD-mimetic macroporous foam for adipose tissue engineering applications. (October 2016) - Rossi, Eleonora; Gerges, Irini; Tocchio, Alessandro; Tamplenizza, Margherita; Aprile, Paola; Recordati, Camilla; Martello, Federico; Martin, Ivan; Milani, Paolo; Lenardi, Cristina
Abstract: Despite clinical treatments for adipose tissue defects, in particular breast tissue reconstruction, have certain grades of efficacy, many drawbacks are still affecting the long-term survival of new formed fat tissue. To overcome this problem, in the last decades, several scaffolding materials have been investigated in the field of adipose tissue engineering. However, a strategy able to recapitulate a suitable environment for adipose tissue reconstruction and maintenance is still missing. To address this need, we adopted a biologically and mechanically driven design to fabricate an RGD-mimetic poly(amidoamine) oligomer macroporous foam (OPAAF) for adipose tissue reconstruction. The scaffold was designed to fulfil three fundamental criteria: capability to induce cell adhesion and proliferation, support of in vivo vascularization and match of native tissue mechanical properties. Poly(amidoamine) oligomers were formed into soft scaffolds with hierarchical porosity through a combined free radical polymerization and foaming reaction. OPAAF is characterized by a high water uptake capacity, progressive degradation kinetics and ideal mechanical properties for adipose tissue reconstruction. OPAAF's ability to support cell adhesion, proliferation and adipogenesis was assessed in vitro using epithelial, fibroblast and endothelial cells (MDCK, 3T3L1 and HUVEC respectively). In addition, in vivo subcutaneous implantation in murine model highlighted OPAAF potential to support both adipogenesis and vessels infiltration. Overall, the reported results support the use of OPAAF as a scaffold for engineered adipose tissue construct.